Expression of SIRT3 in various glial cell types in the periventricular white matter in the neonatal rat brain after hypoxia. (June 2018) - Li, Xiu-Hua; Liu, Shun-Jin; Liu, Xiao-Yu; Zhao, Hai-Yu; Yang, Mao-Geng; Xu, De-Xin; Guo, Jing; Li, Jing-Hui; Li, Juan-Juan
Highlights: Glial cells in the corpus callosum in neonatal rats constitutively expressed SIRT3. SIRT3 immunofluorescence was enhanced in activated microglia, astrocytes and oligodendrocytes in neonatal rats subjected to hypoxia. Expression level of SIRT3 protein in the corpus callosum rich in various glial cell types was increased after hypoxia. Increased SIRT3 expression in various glial cells may be protective against oxidative and inflammatory damage induced by hypoxia. Abstract: Sirtuin 3 (SIRT3) mediates cellular resistance toward various forms of stress. SIRT3 expression in the developing brain, especially its localization in various glial cell types, has not been fully explored. This study aimed to determine SIRT3 expression in the brain of neonatal rats subjected to hypoxia. By immunohistochemistry, immunofluorescence and Western blotting, we show here that SIRT3 expression in the periventricular white matter was up-regulated in hypoxia group compared with the control group at the corresponding time points. Intense SIRT3 expression was detected in microglia at early time points after hypoxia whose cell number was increased with reduced ramifications in hypoxia group compared with the control group. Furthermore, SIRT3 immunoreactivity was obviously enhanced at 24 h, 3 and 7d, but was declined at 14d after hypoxia so that SIRT3 expression between the two groups was comparable. SIRT3 immunofluorescence was also localized in astrocytes labeled with GFAP which was augmented at different time points in hypoxia group. GPAP positive astrocytes exhibited long extending processes being most pronounced at 3d. SIRT3 was moderately expressed at 24 h, 3 and 7d, but was markedly increased at 14d after hypoxia. Moderate SIRT3 expression was also localized in oligodendrocytes labeled with CNPase in the control group. The incidence of CNPase positive oligodendrocytes showing colocalization of SIRT3 increased significantly at 24 h, 3 and 7d after hypoxia. In conclusion, SIRT3 expression was differentially up-regulated in all three major glial cell types following hypoxia. It is suggested that increased SIRT3 expression in the respective glial cell types following hypoxia is involved in different signaling pathways that protect against hypoxic stress in the developing brain.